Sonication parameters for detachment and study of biocorrosionÂ´s biofilms - Vargas, Andreína; Duque, Zoilabet; de Romero, Matilde (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This work presents an experimental design that allows to obtain efficient results for such biofilm detachment employing the sonication technique. For this, 85% was established as the acceptable minimum efficiency of viable cells removed. Bacterial biofilms of the sulphate-reducing bacterium Desulfovibrio termitidis were developed for 24 hours on iron sheets and coupons of carbon steel of different geometries. Maximum efficiencies of detachment with sonication and scrapped ultrasound were compared. The evaluation of the different sonication equipment variables permitted to reach efficiencies above the established rank. The parameters that permitted to obtain a maximum efficiency of 88% were: total time 1 minute, impulse “on” 5 seconds, impulse “off” 10 seconds and 65% of amplitude for the iron sheets and the coupons of carbon steel of rectangular geometry and: total time 2 minutes, impulse “on” 2,5 seconds, impulse “off” 10 seconds and 70% of amplitude for the coupons of concave carbon steel geometry. Additionally, the sonication technique resulted to be 10 times more effective than the technique of scraped-ultrasound at exponential levels.